Social networks as a fundamental tool for selling groceries in Duran markets - Chabusa Vargas, Jorge Luis (2024)
The pandemic and the social problems that have occurred in the country have had a negative impact on the economy, causing several businesses to show a decrease in sales, therefore, many have opted to use ICT to sell products, achieving positive results. Therefore, the main objective of this research is to present the relevance of social networks to carry out commercial transactions, so they could continue to survive in an environment that is constantly innovating. The research was developed in the markets "Marianita de Jesús", "Cdla. Maldonado" and "Las Manuelas", a quantitative approach, an exploratory and descriptive study and a non-experimental cross-sectional design were used. For data collection, customers and merchants belonging to these establishments were surveyed. The main findings reveal that most of them have knowledge about social networks, demonstrating the relevance they have nowadays. In addition, 78.57% of merchants and 77.09% of customers are interested in using them as a means of buying and selling. In short, social networks are a great support for developing processes of marketing, sales and customer service in an efficient way.